2014
DOI: 10.1057/sth.2014.3
|View full text |Cite
|
Sign up to set email alerts
|

The social support model for people with chronic health conditions: A proposal for future research

Abstract: Social support is an important component of health care for people with chronic health conditions. Previous research has described the types of messages created in support groups and found evidence for positive health outcomes of social support. Social support has been conceptualized in myriad ways, however, making it difficult to have a unified body of research. I propose a model to explain how the social support process works for people with chronic health conditions. I articulate what facets of the social s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…It is noteworthy to mention that the degree of support provided by spouses is different to the extent that some spouses even provide extravagant support. Spouses' extravagant support is harmful and associated with lower self-efficacy, lower perceived control over the underlying disease, and greater risk for experiencing anxiety and depression (27). This finding is consistent with the findings of another study conducted in Iran (28).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy to mention that the degree of support provided by spouses is different to the extent that some spouses even provide extravagant support. Spouses' extravagant support is harmful and associated with lower self-efficacy, lower perceived control over the underlying disease, and greater risk for experiencing anxiety and depression (27). This finding is consistent with the findings of another study conducted in Iran (28).…”
Section: Discussionsupporting
confidence: 89%
“…This type of support was of paramount importance to the participants. Previous studies also showed that patients considered their marital partners as the most important source of support to them (11,23,26,27). Spouses are uniquely positioned in their partners' medical regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to practical help, social support also constitutes an important psychological protective factor in coping with haemophilia (emotional base, future prospects, having someone to live for, having someone to turn to when needing help). Studies dealing with other chronic diseases, diabetes, or cancer, arrived at the same conclusion with respect to the impact of social support on psychological health 28‐30 . Reliable, high‐quality social support can enhance resilience to stress, help protect against trauma‐related psychopathology, decrease the functional consequences of trauma‐induced disorders (such as posttraumatic stress disorder) and reduce medical morbidity and mortality 31 .…”
Section: Discussionmentioning
confidence: 88%
“…Since KC women are often in similar situations and environments, it is thought that there is a high frequency of network support interactions like real-life-related topics between participants [ 38 ]. Thus, to approach migrant populations within this environment, network support can be hypothesized to impact health promotion [ 39 ].…”
Section: Discussionmentioning
confidence: 99%